PENGARUH POTONGAN HARGA TERHADAP KEPUTUSAN KONSUMEN DI INDOMARET SIMPANG LIMA KOTA BENGKULU - Selviani, Ayudho; Duharman, Duharman; Sanjaya, Aldo Hendrike (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This research aims to determine the effect of price discounts on consumer decisions at Indomaret Simpang Lima, Bengkulu City. The approach in this research is quantitative research. The population in this research is consumers who shop with a sample of 48 people. Data collection techniques in this research are observation, questionnaires and interviews. The data analysis technique uses averages, simple linear regression analysis, and coefficient of determination using SPSS version 21. The results of this study show that the average price discount is in the strongly agree category that at Indomaret Simpang Lima, City. Bengkulu has many price discounts, the discounts given also vary from time to time and there are also price discounts at certain times and the average of consumer decisions is in the category of strongly agreeing to make purchasing decisions at Indomaret Simpang Lima. Bengkulu city because the price discounts given are in accordance with needs and are also useful and of course consumers will make repeat purchases and from the results of data analysis, it shows that there is a significant influence of price discounts on consumer decisions. The magnitude of the influence of the price discount variable on consumer decisions is 47.5%.